Relation between achievement motivation and sense of purpose with permanence of teenage mothers on the Costa Rican education system, a contribution from counseling - Badilla-Marín, Ester (2017)
This article derives from the research project titled “Features of the meaning of life that favor the permanence of teenage mothers in the formal education system”. Its main objective was to analyze the features of the sense of life, motivation and a sense of purpose, as the most influential factors for the retention of teenage mothers in the formal education system. We worked from an interpretive paradigm, with a qualitative approach and phenomenological method. The information was collected by using techniques such as in-depth interviews and focus groups applied to eleven adolescent mothers aged between 14 and 17 years old; they were students in the formal public education system, day mode, from three urban institutions located in San Jose’s Greater Metropolitan Area, Costa Rica. The research was conducted in the months of October and November, 2015. The results allow identifying the traits of the meaning of life: achievement motivation and a sense of purpose as the most decisive factors for these girls to remain in the high school; also the work and the contribution that the profession of counseling can promote is highlighted.